The Impact of Outdoor Environmental Factors on Indoor Air Quality in Education Settings: A Systematic Review - Jan Rožanec; An Galičič; Andreja Kukec (Atmosphere)
Poor indoor air quality (IAQ) in schools is associated with pupils’ health and their learning performance. This study aims to provide an overview of the outdoor factors that affect the IAQ in educational settings in order to develop public health measures. We conducted a systematic literature review to investigate the outdoor factors that affect IAQ in educational settings. The selection of articles included 17,082 search string hits from the ScienceDirect database published between 2010 and 2023, with 92 relevant studies selected based on the inclusion and exclusion criteria. Based on a systematic review of the literature, we identified the following outdoor factors: proximity to busy roads, commercial and industrial establishments, meteorological conditions, compounds from the natural environment, emissions from heating buildings, atmospheric reactions and secondary pollutants, unpaved school playgrounds, and smoking. This study provides key information on the mentioned outdoor factors and gives recommendations on measures to reduce classroom pollutant concentrations while highlighting educational settings that require special attention. Our study shows that classroom IAQ is affected by many outdoor pollutant sources, the prevalence of which depends on the educational setting’s micro location. Therefore, it is essential to develop an appropriate classroom ventilation strategy for each educational setting.